Does the Structural Water within Gypsum Remain Crystalline at the Aqueous Interface? - Söngen, H.; Silvestri, A.; Roshni, T.; Klassen, S.; Bechstein, R.; Raiteri, Paolo; Gale, Julian; Kühnle, A. (AMER CHEMICAL SOC, 2021)
Solid-liquid interfaces are omnipresent in nature and technology. Processes occurring at the mineral-water interface are pivotal in geochemistry, biology, as well as in many technological areas. In this context, gypsum—the dihydrate of calcium sulfate—plays a prominent role due to its widespread distribution in the Earth’s crust and its manifold applications in technology. Despite this, many fundamental questions regarding the molecular-scale structure, including the fate of the crystal water molecules at the aqueous interface, remain poorly studied. Here, we present an atomic force microscopy (AFM) and molecular dynamics (MD) investigation to elucidate molecular-level details of the gypsum-water interface. Three-dimensional AFM data shed light into the hydration structure, revealing one water molecule per surface unit cell area in the lowest layer accessible to experiment. Comparing with simulation data suggests that the AFM tip does not penetrate into the surface-bound layer of crystal water. Instead, the first hydration water layer on top of the crystal water is mapped. Our findings indicate that the crystal water at the interface remains tightly bound, even when in contact with bulk water. Thus, the interfacial chemistry is governed by the crystal water rather than the calcium or sulfate ions.